İnflamatuvar barsak hastalığı ile polinöropati birlikteliğinin araştırılması - Çetinkaya, Yılmaz (My University, 2008)
İnflamatuar barsak hastalıkları multipl sistemleri tutan, kronik, tekrarlayan hastalıklardır. Polinöropati en sık görülen nörolojik manifestasyondur. Bu çalışmanın amacı inflamatuvar barsak hastalığı ile polinöropati birlikteliğini araştırmaktı. 40 inflamatuvar barsak hastalığı olan olgu ( 20 ülseratif kolit, 20 crohn hastalığı ) ve 24 sağlıklı bireyi çalışmaya aldık. Hasta grubunda polinöropati semptom ve klinik bulgusu yoktu. Hasta grubunun B12 vitamin düzeyi normaldi ve metranidazol kullanmıyorlardı. Sağlıklı kişiler ile karşılaştırıldığında hasta grubunda sağ median sinir distal motor latans, ileti hızı ve F-minimum latansları arasında anlamlı olarak anormal bulundu. Hasta ve kontrol grubunun sağ tibial motor sinir ileti hızı arasında anlamlı farklılık mevcuttu. Hasta ve kontrol grubunun sağ peroneal sinir bileşik kas aksiyon potansiyeli amplitüdü (BKAP) arasında da anlamlı farklılık vardı. Hasta grubunun sağ median, ulnar ve sural duysal sinir aksiyon potansiyeli amplitüdü düşük ve duysal ileti hızı yavaştı. Polinöropati inflamatuvar barsak hastalığının manifestasyonudur ve patogenezinde olasılıkla otoimmunite mevcuttur. Polinöropati ile ilişkili bazı bulgular sadece elektrofizyolojik incelemede görülebilir. Polinöropati demiyelinizan, aksonal veya miks tipte olabilir.

Association of Inflammatory Bowel Diseases and Peripheral Polyneuropathy Inflammatory bowel diseases (IBD) are chronic, recurrent disorders involving multiple systems. Polyneuropathy is the most common neurological manifestation. The aim of this study was to investigate the association of polyneuropathy and IBD in patients with intestinal complications. We studied 40 patients with IBD (20 ulcerative colitis, 20 Crohn’s disease) and 24 healthy subjects. The patients had no clinical sign and symptom of polyneuropathy. They had normal serum levels of vitamin B12 and they were not using metronidazole. The mean distal motor latencies, conduction velocities and F wave minimum latencies of the right median nerve were significantly found abnormal in the patient group comparing with healthy subjects. There was significant difference in motor conduction velocity of the right tibial nerve between patients and controls. Significant differences were found in distal compound muscle action potential (CMAP) amplitude of the right peroneal nerve between patient and control groups. Sensory nerve action potential amplitudes and conduction velocities of the right median, ulnar and sural nerves were significantly lower in the patients. Polyneuropathy is a manifestation of inflammatory bowel disease and the pathogenesis is probably autoimmune. Some findings consistent with polyneuropathy can be only observed on electrophysiological evaluation. Neuropathy can be either demyelinating, axonal or mixed type.
Keywords: Elektromiyografi; Inflamatuvar barsak hastalığı; Polinöropati